2017
DOI: 10.1002/ajmg.a.38513
|View full text |Cite
|
Sign up to set email alerts
|

Congenital limb deficiencies and major associated anomalies in Alberta for the years 1980–2012

Abstract: There is a wide range of the proportion of congenital anomalies associated with limb deficiencies reported in the literature. This variation is primarily attributed to methodology and classification differences. The distribution of associated anomalies among cases with congenital limb deficiencies in Alberta born between January 1, 1980 and December 31, 2012 is described. Of the 170 cases identified, most were live born (75.3%), male (61.8%), had longitudinal limb deficiencies (78.8%), and had associated anoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
2
6
1
2
Order By: Relevance
“…Many previous studies have described associated anomalies in patients with LRD, but with a large range [12, 13, 1519]. In our study, associated anomalies were poorly registered during 1970–1998.…”
Section: Discussioncontrasting
confidence: 54%
“…Many previous studies have described associated anomalies in patients with LRD, but with a large range [12, 13, 1519]. In our study, associated anomalies were poorly registered during 1970–1998.…”
Section: Discussioncontrasting
confidence: 54%
“…LRDs of one limb less often have a genetic cause, compared to LRDs of multiple limbs (Cobben, Hiemstra, & Robinson, 1994; Firth & Hurst, 2017; Harper, 2010), but only few studies have substantiated this. Previous epidemiological studies regarding LRDs have reported prevalence rates (general and per subcategory), the affected side (left: right ratio), symmetry, associated malformations, and diagnoses (Alberto, Barbero, Liascovich, Bidondo, & Groisman, 2020; Bedard, Lowry, Sibbald, Crawford, & Kiefer, 2018; Bedard, Lowry, Sibbald, Kiefer, & Metcalfe, 2015; Evans, Vitez, & Czeizel, 1994; Klungsoyr et al, 2019; Koskimies, Lindfors, Gissler, Peltonen, & Nietosvaara, 2011; Vasluian et al, 2013). To our knowledge there has only been one retrospective cohort study, which analyzed diagnosis rates in patients with uni‐ versus bilateral preaxial longitudinal defects of the upper limb ( n = 119) (James, Green, McCarroll, & Manske, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Limitations to this study include the report period is until hospital discharge without a systematic follow‐up; absence of a screening protocol for syndromic features; and heterogeneity in the access to genetic testing and evaluation by a clinical geneticist (Duarte et al, ). These factors may explain the low proportion of syndromic LRD, and the high proportion of patients with associated CA (39.2%) when comparing to the literature (20–30%) (Bedard et al, ).…”
Section: Discussionmentioning
confidence: 92%
“…There are other reports in the literature detailing associated CA in patients with LRD (Bedard, Lowry, Sibbald, & Kiefer, ; Calzolari et al, ; Evans et al, ; Klungsøyr et al, ; Rosano et al, ; Stoll et al, ; Vasluian et al, ). There are methodological differences that impede an adequate comparison, particularly regarding the exclusion of syndromic cases from the analysis.…”
Section: Discussionmentioning
confidence: 96%